A thousand tomorrows : a novel - Kingsbury, Karen (New York : Center Street, 2005)
"A young couple faces the challenge of falling in love, while seemingly doomed to repeat the negative patterns they have established for most of their lives"--Provided by the publisher.
Keywords: Self-destructive behavior -- Fiction; Psychological fiction; Love stories